Weblog “How Do I Breathe?”—Design and View Statistics - de Luccas, Gabriele Ramos; Berretin-Felix, Giédre; Fukushiro, Ana Paula (International Archives of Otorhinolaryngology, 2019)
Introduction Breathing is one of the vital functions of the body and is essential for the maintenance of life. Preventive measures for respiratory disorders can be used by the population, as well as early self-diagnosis and immediate search for treatment based on knowledge of this subject.Objective this study developed a weblog on the breathing function targeting young people and analyzed the statistical data of views until the present moment.Methods The weblog was developed, and the stages of analysis, design, development and implementation were followed. All texts were evaluated by the Flesch Reading Index to verify the language, and the statistical data were analyzed by the number of views, countries with the highest number of views, search terms used, most viewed pages and number of comments on the blog.Results Issues related to the breathing function and those most cited in the literature were selected. The blog was structured using pages with content and curiosities, with texts with minimum readability of 50%, and was made available on the internet by means of the Wordpress tool. The statistics showed an increase in the number of visits after August 2015; the countries with the highest number of views were Brazil, United States and Portugal; the search terms used were unknown or related to mouth breathing; the most viewed pages related to mouth breathing and the comments addressed questions on mouth breathing, reports and compliments.Conclusion The blog “How do I breathe?,” aimed at young people and containing information about the breathing function, was developed and is available on the internet at the address: https://comoeurespiro.wordpress.com.
Keywords: oral breathing; telemedicine; internet; speech; language and hearing sciences